Gallium enhances reconstructive properties of a calcium phosphate bone biomaterial. (23rd May 2017) - Strazic Geljic, Ivana; Melis, Nicolas; Boukhechba, Florian; Schaub, Sébastien; Mellier, Charlotte; Janvier, Pascal; Laugier, Jean‐Pierre; Bouler, Jean‐Michel; Verron, Elise; Scimeca, Jean‐Claude
Abstract: Calcium phosphate (CaP)‐based biomaterials are commonly used in bone reconstructive surgery to replace the damaged tissue, and can also serve as vectors for local drug delivery. Due to its inhibitory action on osteoclasts, the semi‐metallic element gallium (Ga) is used for the systemic treatment of disorders associated with accelerated bone resorption. As it was demonstrated that Ga could be incorporated in the structure of CaP biomaterials, we investigated the biological properties of Ga‐loaded CaP biomaterials. Culturing bone cells on Ga–CaP, we observed a decrease in osteoclast number and a downregulation of late osteoclastic markers expression, while Ga–CaP upregulated the expression of osteoblastic marker genes involved in the maturation of bone matrix. We next investigated in vivo bone reconstructive properties of different Ga‐loaded biomaterials using a murine bone defect healing model. All implanted biomaterials showed a good osseointegration into the surrounding host tissue, accompanied by a successful bone ingrowth and bone marrow reconstruction, as evidenced by histological analysis. Moreover, quantitative micro‐computed tomography analysis of implants revealed that Ga enhanced total defect filling. Lastly, we took advantage for the first time of a particular mode of non‐linear microscopy (second harmonic generation) to quantify in vivo bone tissue reconstruction within a CaP bone substitute. By doing so, we showed that Ga exerted a positive impact on mature organized collagen synthesis. As a whole, our data support the hypothesis that Ga represents an attractive additive to CaP biomaterials for bone reconstructive surgery. Copyright © 2017 John Wiley & Sons, Ltd.